2017
DOI: 10.1155/2017/1362491
|View full text |Cite
|
Sign up to set email alerts
|

Discoloration Effects of High-Dose γ-Irradiation and Long-Term Thermal Aging of (U)HMW-PE

Abstract: Two polyethylene types with ultra-high (UHMW-PE) and high molecular weight (HMW-PE) used as neutron radiation shielding materials in casks for radioactive waste were irradiated with doses up to 600 kGy using a 60 Co gamma source. Subsequently, thermal aging at 125∘ C was applied for up to one year. Degradation effects in the materials were characterized using colorimetry, UV-Vis spectroscopy, IR spectroscopy, and DSC. Both materials exhibited a yellowing upon irradiation. The discoloration of UHMW-PE disappear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Multiple factors influenced the crystallinity and oxidative degradation by irradiation [61,62]. The dose and dose rate of irradiation strongly influence the crystallinity and oxidation of UHMWPE [55,[63][64][65][66][67][68][69]. A suitable post-irradiation process eliminates free radicals to prevent degradation of UHMWPE over the long period and to promote the stability against oxidation.…”
Section: Crosslinking and Crystallinitymentioning
confidence: 99%
“…Multiple factors influenced the crystallinity and oxidative degradation by irradiation [61,62]. The dose and dose rate of irradiation strongly influence the crystallinity and oxidation of UHMWPE [55,[63][64][65][66][67][68][69]. A suitable post-irradiation process eliminates free radicals to prevent degradation of UHMWPE over the long period and to promote the stability against oxidation.…”
Section: Crosslinking and Crystallinitymentioning
confidence: 99%
“…When analyzing the UV-C light effect over the polymers, it was observed that this kind of material tended to get a yellowish color after some exposure time, as occurred in variety of polymers in other works [18][19][20][21]. This behavior was observed not only visually but also quantitatively.…”
Section: Colorimetry Testmentioning
confidence: 75%
“…Polyethylene (PE) is used largely in the radiation-technology industry; therefore, the effects of ionizing radiation on it have been extensively studied [ 16 , 17 , 18 ]. Fluoropolymers exhibit excellent chemical/thermal properties and weathering due to the high bonding energy of carbon and fluorine, and the high values of fluorine electronegativity and electron density [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%